Carrageenans from Nuclear Phases of Subantartic Mazzaella Laminarioides (Gigartinales, Rhodophyta) and Graft Copolymerization of Alkali-Modified Carrageenan with Acrylamide - Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Yanez-Sanchez, M; Torres-De la Fuente, R (Springer Netherlands, 2016)
Aqueous extraction of cystocarpic, tetrasporic, and vegetative individuals of Mazzaella laminariodes collected in the Magellan Ecoregion, Southern Chile, afforded sulfated galactans. Analysis by Fourier transform infrared spectroscopy (FT-IR) and by 1H and 13C NMR spectroscopy indicated that purified extracts from cystocarpic (CP) and vegetative individuals (VP) were mixtures of κ/ι-type carrageenans and their precursors μ- and ν-carrageenans, whereas the aqueous extract from tetrasporic individuals was a λ-type carrageenan. Alkaline treatment of CP and VP polysaccharides produced modified polysaccharides with lower content of sulfate groups and with a concomitant increase of 3,6-anhydrogalactose content; analysis by 2D 1H and 13C NMR indicated the presence of hybrid κ-ι-carrageenans. Copolymerization of alkali-treated CP carrageenan with acrylamide was achieved by using ceric ammonium nitrate as the initiator; studies by NMR spectroscopy indicated grafting of polyacrylamide at position C-6 of β-galactopyranosyl residues. Reaction of modified CP with acrylamide assisted by microwave irradiation in the presence of ammonium persulfate afforded a copolymer grafted at position C-2 of β-galactopyranosyl residues. © 2015, Springer Science+Business Media Dordrecht.